KECEMASAN BERLEBIH TERHADAPREMAJA PELAKU PENGGEROYOKAN DAN PEMBUNUHAN DI KAB. TONDANO - Rinna Yuanita Kasenda; Feronika Posumah; Irnawati Mine’; Aldinata (Jurnal Genta Mulia, 2024)
This article discusses the excessive anxiety of stabbing perpetrators, especially teenagers who are involved in criminal acts. This research uses a qualitative approach and analyzes changes in attitudes and attitudes towards teenagers involved in murder cases. The article also discusses theories related to juvenile delinquency and feelings of regret. Research methods include observation, interviews, and evaluation. This research focuses on perpetrators of criminal acts of beatings and murders who physically assaulted the victims until they died. The perpetrator experienced excessive anxiety after being arrested and sentenced to prison, and was afraid of intimidation from local residents. This anxiety causes changes in behavior to become closed and anti-social. This study concludes that threats and social sanctions against criminals can cause prolonged fear and regret, as well as changes in behavior to being closed and avoiding other people.